Menjadi oang tua positif bagi anak: Penggunaan aplikasi Canva pada perkembangan kognitif anak prasekolah - Rahmania, Alfi Najmi (Maliki Interdisciplinary Journal, 2024)
Being a Positif parent needs to involve providing constructive support and encouragement to children in various aspects of development, including cognitive development at preschool age. One modern way to support this development is through the use of creative technology such as the Canva application. Canva, a user-friendly graphic design application, can be used to develop creativity, improve fine motor skills, introduce the concept of color and shape, and enrich children's vocabulary and language skills. By actively participating and providing support in using Canva, parents can create a fun and interactive learning experience for their children. This approach not only develops the child's technical and creative skills, but also strengthens the emotional bond between parent and child, creating a positive environment for optimal cognitive development.